Extracellular vesicles in a maze of glycomic complexity - Danilović Luković, Jelena; Janković, Tamara; Mitić, Ninoslav; Goč, Sanja (Biologia Serbica, 2022)
The carbohydrate portion of proteins and lipids mediates a variety of biological processes. Revealing their underlying principles is a challenging task that could contribute to a better understanding of many patho/physiological conditions. On the other hand, the interest in extracellular vesicles (EVs) has increased in recent years due to their involvement in intercellular communication leading to an array of functional and structural changes in recipient cells. Their characterization uncovered an exceptional diversity in size, morphology, as well as in membrane and cargo content. Monitoring/analysis of surface glycosylation of EVs originating from the prostate, termed prostasomes, revealed their substantial contribution to the complexity of seminal plasma (SP) glycome. Heterogeneity of surface glycans confirm the existence of several prostasome subpopulations. Presentation of surface glycans on prostasomal membrane is strongly affected by co-localized membrane-associated glycoproteins and tetraspanins. They appear to be organized in established/regular distribution patterns on membrane domains. Surface glycans are a component of EVs membrane that affects its functionality and potentially a distinction marker of prostasome subpopulations. Further understanding of the complex composition of glycans on EVs might explain the relation of their structure with functional alterations in distinct patho/physiological conditions.